2013
DOI: 10.1002/humu.22460
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Identifies Potential Risk Variants for Mendelian Disorders at High Prevalence in Qatar

Abstract: Exome sequencing of families of related individuals has been highly successful in identifying genetic polymorphisms responsible for Mendelian disorders. Here, we demonstrate the value of the reverse approach, where we use exome sequencing of a sample of unrelated individuals to analyze allele frequencies of known causal mutations for Mendelian diseases. We sequenced the exomes of 100 individuals representing the three major genetic subgroups of the Qatari population (Q1 Bedouin, Q2 Persian-South Asian, Q3 Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 34 publications
3
51
0
Order By: Relevance
“…The aim of this study is to analyse a series of inbred Qatari families, mainly belonging to the genetic cluster consistent with Arabian origin or Bedouin [6] , by using the homozygosity mapping process to identify genomic regions that potentially harbour an excess of deleterious mutations. Previous studies [7,8] have demonstrated that in Qatari samples, many predicted deleterious SNPs occur at significantly high frequencies, providing useful information for the epidemiological profile of this population. Moreover, the Qatari population has recently evolved from three tribes from Persia, the Arabian Peninsula, and Oman.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is to analyse a series of inbred Qatari families, mainly belonging to the genetic cluster consistent with Arabian origin or Bedouin [6] , by using the homozygosity mapping process to identify genomic regions that potentially harbour an excess of deleterious mutations. Previous studies [7,8] have demonstrated that in Qatari samples, many predicted deleterious SNPs occur at significantly high frequencies, providing useful information for the epidemiological profile of this population. Moreover, the Qatari population has recently evolved from three tribes from Persia, the Arabian Peninsula, and Oman.…”
Section: Introductionmentioning
confidence: 99%
“…These molecular findings confirm previous epidemiological studies showing that, in the Qatari population, there is a rate of consanguinity of 51% in the present generation with a coefficient of inbreeding of 0.023724 [2] . Very recently, data on whole exome sequencing of 100 individuals representing the 3 major genetic subgroups of the Qatari population (Q1, Q2 and Q3) have been reported [3] . By this approach, RodriguezFlores et al [3] identified 37 variants in 33 genes with effects on 36 clinically significant Mendelian diseases, including variants not present in the 1000 Genomes Project [http://www.1000genomes.org/] and high-frequency variants when compared to the 1000 Genomes Project populations.…”
mentioning
confidence: 99%
“…Very recently, data on whole exome sequencing of 100 individuals representing the 3 major genetic subgroups of the Qatari population (Q1, Q2 and Q3) have been reported [3] . By this approach, RodriguezFlores et al [3] identified 37 variants in 33 genes with effects on 36 clinically significant Mendelian diseases, including variants not present in the 1000 Genomes Project [http://www.1000genomes.org/] and high-frequency variants when compared to the 1000 Genomes Project populations. Several of these Mendelian variants were specific of one Qatari subgroup, and they were further confirmed in an independent population of 386 Qatari individuals [3] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Projects such as the Qatar-based Weill Cornell Medical Study (Rodriguez-Flores et al 2013) and the Singapore Genome Variation Project (Teo et al 2009) sequenced population samples as small as 100 and 268 individuals, respectively, whereas President Obama's Precision Medicine Initiative Cohort Program, announced in early 2015, aims to sequence the genomes of 1 million Americans. 48 In the UK, the 100,000 Genomes Project is focusing on 100,000 genomes of patients with rare diseases and their families, and patients with cancer, 49 and the Human Heredity and Health in Africa Initiative aims to sequence 50,000-75,000 genomes (H3Africa Consortium 2014, 1347) (see Table 3 in the Appendix).…”
mentioning
confidence: 99%